Perfil de enfermeiras(os) acerca das práticas integrativas e complementares e o cuidado às pessoas com hipertensão arterial: estudo de métodos mistos - Wickert, Daiana Cristina (2022)
The general objective is to analyze the educational and professional profile of nurses about integrative and complementary health practices and understand how they use them in the care of people with arterial hypertension. This is a mixed methods, sequential explanatory research (QUAN-qual notation), linked to a multicenter project supported by CNPq, developed with nurses from Santa Catarina. Held from 06/16/2021 to 10/15/2021, the quantitative step was transversal, through a virtual questionnaire. Data were analyzed using SPSS® 26.0 and Epi Info™ 7.2 software, in a descriptive and inferential manner. The measure of association was the prevalence ratio (95% confidence interval and significance p ≤0.05). The tests used were: Chi-square, Fisher's test (for samples smaller than five in each subcategory), Student's T (if the independent variable was continuous, the categorical dependent variable and standard deviations were found to be equal (no difference statistic)). The qualitative stage was carried out from 11/01/2021 to 12/20/2021 through semi-structured virtual interviews and construction of narratives with nurses trained in integrative and complementary practices and who use them in the care of people with hypertension , selected by lot in the seven macro-regions of health. The analysis was participatory with the feedback from the narratives. Ethical precepts were followed. A total of 386 nurses responded to the questionnaire, of which 142 have training in integrative and complementary practices and 76 use them in their work routines and more frequently in Primary Health Care. There was a predominance of women, white, Catholic, married, working as public servants in a 40-hour week, with an individual income of three to four minimum wages, trained as nurses for more than 60 months. Most had their first training in integrative and complementary practices from 2013 to 2022, prevailing in people who had a graduate degree when compared to nurses who had only a degree (p=0.003). 55 nurses reported using integrative and complementary practices in the care of people with hypertension, aiming at integral balance, with effects on anxiety, stress, sleep and rest. For hypertensive crisis, there is an emphasis on the bleeding technique of auriculotherapy. In the narratives of the 18 interviewees, individualized movements were evidenced, as well as personal financial investment for training, with auriculotherapy prevailing. The educational and professional profile regarding integrative and complementary practices is similar to the general profile of nurses, however, with a focus on comprehensive care. It is understood that integrative practices are used in the care of people with hypertension in an incipient way, considering their potential as a resource in nursing care. The research contributes by composing the evidence already available and strengthening the role of nurses in integrative and complementary practices. Such findings can provide subsidies for the construction of minimum parameters for the training of nurses in integrative and complementary practices, helping in the elaboration of resolutions for professional practice compatible with reality, as well as contributing to the elaboration of protocols for professional practice. They can also make it possible to define criteria for supplementing training, through permanent health education strategies, aiming at the incorporation of the best current scientific evidence.